COLONISATION, DECOLONISATION AND THE CHALLENGES OF ENGENDERING AN AFRICAN DEMOCRATIC CULTURE - CLEMENT ODIRI OBAGBINOKO (International Studies Journal, 2025)
During colonialism, many African countries had their territories conquered and subdued by Europe for the primary purpose of exploring, exploiting and establishing economic buffer zone in Africa.  To achieve this, the colonialists introduced and substituted their political and administrative structures for the pre-colonial indigenous African political/administrative structures. This resulted in the adoption of the European model of liberal democracy. The paper discusses the ontology of Africa’s pre-colonial indigenous political system, European colonialism and its attendant adverse effects on the post-colonial African state. The paper rues the aping of Western democratic theory by former African colonies as primarily responsible for the pervasive political crises across Africa. The paper thus recommends a reversion to and the renovation of the pre-colonial African indigenous political institutions as a pathway to engendering an identity for Africa’s democracy. Not a total rejection of the western model of democracy and not a total acceptance of the pre-colonial political institution but a somewhat adoption of a middle course suitable for a typical African socio-cultural milieu.